Proportion-dependent osteogenic activity of electrospun nano-hydroxyapatite/polylactic acid fiber membrane in vitro and in vivo. (July 2022) - Liang, Bangbang; Feng, Tianyi; Yuan, Xiaoting; Zhao, Kang; Li, Chengyu; Han, Yingchao
Graphical abstract: Highlights: nHAP can improve the hydrophilicity of PLA fiber surface and promote cell infiltration. nHAP/PLA fiber membrane shows nHAP proportion-dependent stiffness and osteogenic activity. 6–10 wt% of nHAP in PLA fiber membrane is appropriate for osteogenesis. Severely decreased mechanical property of 20 %nHAP/PLA blocks the osteogenic effect of nHAP. Abstract: The effect of proportion on the physicochemical and osteogenic properties of electrospun nano-hydroxyapatite/polylactic acid (nHAP/PLA) fiber membrane was investigated from 0/100 to 20/80 (nHAP/PLA mass ratio), aiming to optimise the proportion and integrate mechanical support, biodegradability, cell infiltration and osteogenic activity for better bone repair. The results showed the incorporated nHAP increased the hydrophilicity of the fiber surface, and 6–10 wt% nHAP/PLA membrane showed the enhanced modulus in the direction perpendicular to membrane plane. Biological experiments demonstrated the nHAP proportion-dependent osteogenic activity of nHAP/PLA membranes. The addition of 6–10 wt% nHAP in the fiber membrane significantly promoted cell proliferation and differentiation. In vivo experiments of stacked implantation of the membrane displayed multilayer growth in the pure PLA group owing to the hydrophobicity of PLA and single-layer growth in the nHAP/PLA group because the hydrophilicity of the nHAP/PLA membrane improved the adhesion of the layers. The addition of 6–10 wt% nHAP/PLA also promoted cell recruitment and infiltration and increased osteogenesis, with enhancements of 41% in bone tissue volume/total tissue volume and 37% in bone mineral density. Our study provides helpful support for the preparation of composite electrospun membranes with improved osteogenic activity by optimising the organic–inorganic proportion.